Pengaruh Self Efficacy, Prokrastinasi Akademik, dan Prestasi Akademik Terhadap Perilaku Kecurangan Akademik - Depi Apriliyanti; Ai Nur Solihat; Yoni Hermawan (Pendidikan Ekonomi FPEB Universitas Pendidikan Indonesia, 2021)
Academic cheating behavior has become a natural and common thing to happen even though this behavior has serious harm or adverse effects for the perpetrators. So, the importance of this research is to find out what things can affect academic cheating behavior. So that later when they know the cause, students can take preventive actions or can choose the best alternative efforts as a form of preventing cheating. This study aims to determine the effect of self-efficacy, academic procrastination, and academic achievement on students' academic cheating behavior partially and simultaneously. The research method used is a survey method with an explanatory design. The population in this study were students of the 2018 and 2019 Economics Education Department, totaling 219 students. The sampling technique used is proportionate stratified random sampling which is calculated using the Slovin formula. The data collection technique in this study used a questionnaire and the data analysis technique used was multiple linear regression analysis. The results showed that 1) There was a negative and significant effect between self-efficacy on student academic cheating behavior with a significance value of 0.004, 2) There was a positive and significant influence between academic procrastination on student academic cheating behavior with a significance value of 0.000. 3) There is no significant effect between academic achievement on student academic cheating behavior.wi and 4) There is a significant influence between self efficacy, academic procrastination, and academic achievement on student academic cheating behavior